A articulação da tipografia nos gêneros do discurso - Munhoz, João Pedro Gonçalves (2024)
Fonts are sets of characters united by a particular design form, an aesthetic concept, or a specific purpose. They are constructed using complex typographic techniques and allow for the easy production of many of the texts we read and write on a daily basis. As such, a wide variety of fonts are constantly accessed, each with its own specific visual characteristics. Given the prevalence of these typographic products, societies began to develop many conceptions about their use. This work seeks to understand the discursive mechanisms that shape typographic perceptions from an exclusively linguistic perspective, in an approach where the speech genres in which typographic uses occur are the central elements of the analysis. Through the observation of various graphic pieces, representative of different speech genres, the work seeks to describe the roles that typography plays in speech plans. The analysis is based on Bakhtin’s theory of speech genres and looks into the history of genres and typography for hints on possible dialogisms that have come to determine contemporary typographic uses. The work concludes that the typographic layer is a constitutive component of speech genres, having different degrees of relevance depending on the specificities of each speech genre.